ECONOMY HOST IN SUBJECTS MAIN ACTIVITY BENEFIT ACCOUNT - Habibullayev Javohir Abdulla ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. Article farm​ host in subjects main activity benefit account to the subject dedicated. In it household host of subjects financial stability and in development main activity benefit account importance is emphasized. In the article main activity benefit account structural parts and him of calculation importance statement will be done. Also in the article household host in subjects main activity benefit account to improve directed important issues, including automation, standardization, analysis make, expenses manage and development discussion will be done. Article, economy host from subjects own activities more efficient organize to reach and financial stability to provide demand doer main activity benefit account about current data present is enough.